2015
DOI: 10.1002/pra2.2015.145052010072
|View full text |Cite
|
Sign up to set email alerts
|

Perceived outcomes of online parenting information according to self‐selected participants from a population of website users

Abstract: Looking for consumer health/well-being information online is increasingly common. However, little is known about how people are using information targeted to a specific audience, and what happens as a result of this use. We partnered with 'Naitre & Grandir' (N&G), a magazine, website and newsletter offering trustworthy parenting information on child growth, development and health/wellbeing. This study was designed to uncover the outcomes of online parenting information. We used the theory-driven Information As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…In fact, the effectiveness of childhood education interventions has been demonstrated repeatedly [16-19,23,27-47]. In our 2-year pilot data, parents expected health and well-being benefits (for themselves or their child) from using N&G information in 65.4% of all IAM ratings (n=34,021) [50]. In accordance with knowledge translation and implementation research [62], we will not replicate effectiveness studies and rather focus on improving interventions that work.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, the effectiveness of childhood education interventions has been demonstrated repeatedly [16-19,23,27-47]. In our 2-year pilot data, parents expected health and well-being benefits (for themselves or their child) from using N&G information in 65.4% of all IAM ratings (n=34,021) [50]. In accordance with knowledge translation and implementation research [62], we will not replicate effectiveness studies and rather focus on improving interventions that work.…”
Section: Discussionmentioning
confidence: 90%
“…In line with studies on social inequalities in Web information use [55-61], the statistical analysis of these ratings revealed a social gradient: low-SES parents underuse N&G and the IAM (Figure 1). Results also indicated that low-SES parents are more likely to report decreased worries and increased confidence as a result of using N&G information [50]. There is a need to understand this gradient to improve N&G content and reach low-SES parents and a need to explore how the use of knowledge translates into health and well-being outcomes for low-SES parents and children.…”
Section: Introductionmentioning
confidence: 99%
“…Good communication skills may allow people to overcome low levels of e‐health literacy and Internet self‐efficacy (Zach et al, ). Mediated (by someone else) acquisition of information is very common; for example, up to 18.1% of searches for parenting information may be conducted for someone else's child and communicated to the parents (Pluye et al, ). Good communication with health professionals usually leads to better health outcomes (Street, ).…”
Section: Conceptual Boundariesmentioning
confidence: 99%
“…N&G partnered with investigators from McGill University to validate and implement the IAM to continuously assess and improve content shared on the N&G website and newsletter [49][50][51][52][53]. In line with the Canadian Institutes of Health Research (CIHR)'s definitions [54], the IAM is a knowledge translation tool for monitoring N&G information use, and its impact on parents is measured by expected health/well-being benefits.…”
Section: Introduction Rationalementioning
confidence: 99%
“…In line with studies on social inequalities in Web information use [55][56][57][58][59][60][61], the statistical analysis of these ratings revealed a social gradient: low-SES parents underuse N&G and the IAM (Figure 1). Results also indicated that low-SES parents are more likely to report decreased worries and increased confidence as a result of using N&G information [50]. There is a need to understand this gradient to improve N&G content and reach low-SES parents and a need to explore how the use of knowledge translates into health and well-being outcomes for low-SES parents and children.…”
Section: Introduction Rationalementioning
confidence: 99%